Accidents at work and living conditions among solid waste segregators in the open dump of Distrito Federal - Maria da Graça Hoefel; Fernando Ferreira Carneiro; Leonor Maria Pacheco Santos; Muriel Bauerman Gubert; Elisa Maria Amate; Wallace dos Santos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
The work of recycling solid waste segregators allows a precarious livelihood, but triggers a disease process that exacerbates their health and well-being. This study aimed to estimate the prevalence of occupational accidents at the open dump in the Federal District and its associated factors. Most segregators have had an accident at work (55.5%), perceived the danger of their working environment (95.0%) and claimed they did not receive personal protective equipment (51.7%). Among other findings, 55.8% ate foods found in the trash, 50.0% experienced food insecurity at home and 44.8% received Bolsa Família. There was a statistically significant relationship between work accidents and perception of dangerous work environment, household food insecurity and the presence of fatigue, stress or sadness (p < 0.05). On the other hand, the fellowship between the segregators was associated with a lower prevalence of accidents (p < 0.006). Women are the majority of the segregators (56.5%) and reported more accidents than men (p < 0.025). We conclude that the solid waste segregators constitute a vulnerable community, not only from the perspective of labor, but also from the social and environmental circumstances. To reverse this situation, effective implementation of the National Policy of Solid Wastes is imperative, in association with affirmative policies to grant economic emancipation for this population.